2008
DOI: 10.28945/179
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Screencasts and Cognitive Tools as Scaffolding for Novice Object-Oriented Programmers

Abstract: Executive SummaryModern information technology and computer science curricula employ a variety of graphical tools and development environments to facilitate student learning of introductory programming concepts and techniques. While the provision of interactive features and the use of visualization can enhance students' understanding and assist them in grasping fundamental ideas, the real difficulty for many students lies in making the transition from relying on the graphical features of these tools, to actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 47 publications
0
3
1
Order By: Relevance
“…The findings in this study are not in line with previous studies by Lee, et al with the result that there is no significant difference in the effect of screencast [28]. Although the same as demonstrating writing program code step by step, they differ in the level of abstraction of knowledge.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings in this study are not in line with previous studies by Lee, et al with the result that there is no significant difference in the effect of screencast [28]. Although the same as demonstrating writing program code step by step, they differ in the level of abstraction of knowledge.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent decades, computer-based visual representation tools such as concept maps, procedural flowcharts, causal maps, and integrated cognitive maps have been increasingly applied to educational practices and incorporated in computer-based learning environments to foster higher-order thinking and self-directed learning (Lajoie & Derry, 1993;Lee, Pradhan, & Dalgarno, 2008;Spector & Anderson, 2000;Wang, Derry, & Ge, 2017). Such visualisation-based cognitive tools (Jonassen, Carr, & Yueh, 1998) can help represent complex, abstract issues and processes that are difficult to convey in traditional formats.…”
Section: Computer-based Visual Representations As Cognitive Toolsmentioning
confidence: 99%
“…The VR program developed in this study revealed a limitation in developing the communication skills of nursing students based on interactions with other people. Therefore, further studies should be conducted to develop a patient experience–based VR learning program that not only satisfies the expected VR elements—such as spatial recognition, experience-based learning, immersion, context learning, and cooperation learning 33 —but also strengthens the conditions related to interactions. However, the program developed in this study did not use only VR contents, as the intervention—which was based on both PBL and VR—was applied for the virtual experience of nursing students as perioperative patients.…”
Section: Discussionmentioning
confidence: 99%